2012
DOI: 10.1080/03630242.2012.674092
|View full text |Cite
|
Sign up to set email alerts
|

Facets of Career Satisfaction for Women Physicians in the United States: A Systematic Review

Abstract: Women make up a growing proportion of the physician workforce, and their career satisfaction may affect their health. The authors hypothesized that many facets adversely affecting career satisfaction in women physicians were extrinsic, therefore, preventable or modifiable. The authors conducted a systematic review of the literature in English published through February 2010 to examine facets of career satisfaction of U.S. women physicians. The authors used the women physician AND job satisfaction OR career sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
5
42
0
1
Order By: Relevance
“…A systematic review of the subject found that women physicians generally had similar levels of career satisfaction compared to men but were more concerned with a lack of time for relationships with family, similar to the results found here. [19] Another study found most women physicians to be generally satisfied with their careers, similar to results from Table 2. The strongest factor related to satisfaction among women physicians was work control and the youngest physicians were found to have less control.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A systematic review of the subject found that women physicians generally had similar levels of career satisfaction compared to men but were more concerned with a lack of time for relationships with family, similar to the results found here. [19] Another study found most women physicians to be generally satisfied with their careers, similar to results from Table 2. The strongest factor related to satisfaction among women physicians was work control and the youngest physicians were found to have less control.…”
Section: Discussionsupporting
confidence: 75%
“…[19] For instance, being female is associated with lower dissatisfaction among white physicians but higher dissatisfaction among black physicians. Female physicians have lower odds of dissatisfaction than male physicians in rural settings, but this difference is not found in urban ones.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomy is an important feature in the work of the independent primary care midwife and has been identified as a determinant of job satisfaction in our study and other studies (Tyssen et al, 2013;Castaneda and Scanlan, 2014;Hunter and Warren, 2014). Most of the midwives were female, and next to work related factors, more personal characteristics, like having young children at home, or lacking work-life balance can have an impact on feelings of job satisfaction (Emancipatiemonitor, 2012;Rizvi et al, 2012;Robinson, 1993). It may be that perspectives and opportunities for midwives' career advancement are influenced by gender issues in families and organisations.…”
Section: Comparison With Other Researchmentioning
confidence: 81%
“…The community midwives as well as our participating midwives reported that their job was satisfying, that they liked the variety of the work and disliked the long on call hours and the poor work-life balance. Compared with the study of Rizvi et al (2012) on women physicians in the United States both our participating midwives and the women physicians were concerned with perceived lack of time for their own family and relationships with patients. Compared with the study of van Ham et al (2006) on job satisfaction among Dutch general practitioners, both primary care midwives and GPs were pleased with the content of their work and the relation and contact with direct colleagues.…”
Section: Comparison With Other Researchmentioning
confidence: 97%
See 1 more Smart Citation